Raising hell: On the hyper-projectivity of slurs - Beaver, David; Stanley, Jason (Proceedings of the Amsterdam Colloquium, 2022)
Mere mentions of a slur have the potential to do harm, assaulting a listener, perpetuating marginalization of oppressed groups, and solidifying oppressive practices. Whereas most projective meanings, such as presuppositions, are typically assumed to be blocked by quotation, some effects of slurs are found even when the slur is quoted. In this sense, slurs are hyper-projective. Our goal is to explain why. The material here is drawn from: David Beaver and Jason Stanley, The Politics of Language, Princeton University Press (in press), primarily from Chapter 10, "Oppressive Speech."